2019
DOI: 10.3390/educsci9030177
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Competences of Teachers in Big Data in the Era of Digitalized Learning

Abstract: The progress of technology in the field of education has led to the development of new professional skills in the teaching community, such as digital competence. Likewise, it has propagated the appearance of new learning environments mediated by technological resources that favor the generation of a large volume of data, known as Big Data, derived from the interactions of educational agents in virtual environments. This study aims to determine the level of digital competence in the informational area of teache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 57 publications
1
37
0
7
Order By: Relevance
“…The results of the present study indicated a low level of digital competence by the teaching body. None of the dimensions included in digital competence obtained optimal results, which indicates that, as with other educational stages, continuing education teachers also present a low level [33,34]. In particular, the digital content creation dimension showed alarming results, as it was close to zero [37][38][39].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The results of the present study indicated a low level of digital competence by the teaching body. None of the dimensions included in digital competence obtained optimal results, which indicates that, as with other educational stages, continuing education teachers also present a low level [33,34]. In particular, the digital content creation dimension showed alarming results, as it was close to zero [37][38][39].…”
Section: Discussionmentioning
confidence: 88%
“…In this line, there are relevant studies [33,34] that specify a deficient level in the informational area, research, selection, and collection of information. Additionally, they deal with the analysis of digital competence in active teachers, and among them, we can find a compendium of studies in different contexts that determine that teachers do not have enough digital skills according to the current demands of the information society [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…In a context in which the pandemic caused by COVID-19 has had profound consequences on social, economic and cultural life worldwide, in an increasingly digital society [2,3], with the announced Society 5.0 based on digital being a paradigmatic example [4,5], the schooling dimension has also been affected in its normal functioning [6,7,8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The level of acquisition in each area, particularly elementary levels (areas 1 and 2), has a direct impact on teaching activity and on the practical use of ICT [17]- [19]. In particular, older teachers have the added difficulty of lacking technological skills [20], in addition to the limited social and institutional systems, which hinder older adults' ability to acquire experience and ease with technology [21].…”
Section: Introductionmentioning
confidence: 99%